Association of AM-PM Milk Records with Daily Milk Traits in Gir Cows - Agravat, Priyam H; Patbandha, Tapas K; Odedra, Mulraj D; Savsani, Harish H; Maurya, Priyanka; Belim, Saman Y (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Present study evaluated association of morning (AM) and afternoon (PM) milk records with 24 h daily milk traits (milk yields, composition and somatic cells) in Gir cows (n=50). Milk yield, composition and somatic cell count (SCC) were recorded at fortnightly interval. The milk yield did not differ at AM and PM milking sessions, while fat corrected milk yield was significantly (p=0.021) higher at PM than AM milking session. The AM milk had significantly lower fat content (p=0.034), but higher protein (p=0.032), lactose (p=0.011), ash (p=0.004) and solid-not-fat (p=0.009) content than PM milk. Milk total solids content and SCC of AM and PM milk did not differ significantly. All the AM-PM milk traits showed positive and significant (p